(untitled) (Socio-Economic Development Panorama, 2008)
This paper concerns themes with Initial Public Offerings (IPOs) in the Nepalese capital market. The tremendous increase in the public companies has also embraced IPOs in the same pace. This is attributed to meet compulsory requirement schemes of IPOs by the public companies. IPOs are under subscribed. However, that is why IPOs is found to be over subscribed specially in the case of companies in the finance sector. However, there is a significant difference in the approval of IPOs, and issued amount is discovered. The paper eloquently deals with the pattern of IPOs and public awareness in IPOs. Key words: initial public offerings, capital, primary market, IPO of companies, preference share, increased share, capital gain, investment, innovative measures Socio Economic Development Panorama, Vol. 1, No. 3(2008) pp. 21-30